College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 9 - Section 9.5 - The Binomial Theorem - 9.5 Assess Your Understanding: 34

Answer

$-314928$

Work Step by Step

By using the binomial theorem we can expand the algebraic expression in the form of: $(ax+b)^n=\binom{n}{0}a^nb^0x^n+\binom{n}{1}a^{n-1}b^1x^{n-1}+...+\binom{n}{n-i}a^{i}b^{n-i}x^{i}+...+\binom{n}{n-1}a^1b^{n-1}x^1+\binom{n}{n}a^0b^nx^0$ There, we can see that the coefficient of $x^i$ is $\binom{n}{n-i}a^{i}b^{n-i}$. In this case, $a=2$, $b=-3$, $n=9$, $i=2$; therefore, the coefficient will be: $\binom{9}{9-2}2^2(-3)^{9-2}=\binom{9}{7}2^2(-3)^7=36\times 4\times -2187=-314928$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.